Further potential savings attributable to maximum generic substitution of antidepressants in South Africa: A retrospective analysis of medical claims - Elmarie van der Westhuizen; Johanita R. Burger; Martie S. Lubbe; Jan H.P. Serfontein (AOSIS, 2010)
The main objective of the study was to calculate potential cost savings that could have been generated by maximum generic substitution of antidepressants within the private health care sector of South Africa from 2004 to 2006. Data on computerised medicine claims of patients receiving one or more antidepressants during three consecutive years (i.e. 2004, 2005 and 2006) were elicited from a South African pharmaceutical benefit management company. The total study population consisted of 292 071 items (N = 5 982 869) on 273 673 prescriptions (N = 5 213 765) at a total cost of R56 183 697.91(N = R1 346 210 929.00). A quantitative, retrospective drug utilisation review was conducted, and data were analysed using the Statistical Analysis System® programme. Potential cost savings were computed for criteria-eligible substances in the study population. Generic medicine constituted 58.7% (N = 292 071) of all antidepressants claimed, at a total cost of 28.2% (N = R1 346 210 929.00)of all incurred costs. With total substitution of the average price of all criteria-eligible innovators, a potential saving of 9.3% (N = R56 183 697.91) of the actual antidepressant cost over the study period was calculated. In developing countries with limited health care resources, generic medicines can be cost-saving treatment alternatives. Opsomming Die hoofmikpunt van hierdie studie was om die potensiële kostebesparing te bereken wat deur maksimale generiese vervanging van antidepressante in die Suid-Afrikaanse private gesondheidsorgsektor tussen 2004 en 2006 teweeggebring sou kon word. Data oor gerekenariseerde eise vir medisyne van pasiënte wat een of meer antidepressante gedurende die studietydperk ontvang het (d.i. 2004, 2005 en 2006) is van ŉ Suid-Afrikaanse maatskappy wat farmaseutiese voordele bestuur, verkry. Die totale studiepopulasie het bestaan uit 292 071 items (N = 5 982 869)van 273 673 voorskrifte (N = 5 213 765) teen ŉ totale koste van R56 183 697.91 (N = R1 346 210 929.00).'n Kwantitatiewe, retrospektiewe medisyneverbruiksontleding is gedoen en data is geanaliseer deur van die Statistical Analysis System®-pakket gebruik te maak. Potensiële kostebesparings is vir middels in die studiepopulasie wat aan die kriteria voldoen het, bereken. Generiese produkte het 58.7% (N = 292 071) van alle produkte wat voorgeskryf is, uitgemaak, teen ŉ totale koste van 28.2% (N= R1 346 210 929.00). Indien die gemiddelde prys van alle middels wat aan die kriteria vir vervanging voldoen het, met die prys vir generiese middels vervang word, is ŉ potensiële besparing van 9.3%(N = R56 183 697.91) van die werklike koste vir antidepressante gedurende die studietydperk moontlik. Generiese middels kan in ontwikkelende lande met beperkte gesondheidsorg-hulpbronne kostebesparende alternatiewe wees.